Regional variation in clinical characteristics and outcomes in patients with atrial fibrillation: Findings from the ARISTOTLE trial. (1st March 2020) - Bahit, M. Cecilia; Granger, Christopher B.; Alexander, John H.; Mulder, Hillary; Wojdyla, Daniel M.; Hanna, Michael; Goto, Shinya; Xavier, Denis; Verheugt, Freek W.A.; Lanas, Fernando; Hijazi, Ziad; Wallentin, Lars; et al.
Abstract: Background: Variation in patient characteristics and practice patterns may influence outcomes at a regional level. Methods: We assessed differences in demographics, practice patterns, outcomes, and the effect of apixaban compared with warfarin in ARISTOTLE ( n  = 18, 201) by prespecified regions: North America, Latin America, Europe, and Asia Pacific. The primary outcomes were stroke/systemic embolism and major bleeding. Results: Compared with other regions, patients from Asia Pacific were younger, more women were enrolled in Latin America. Coronary artery disease was more prevalent in Europe and Asia Pacific had the highest rate of prior stroke and renal impairment. Over 50% of patients in North America were taking ≥9 drugs at randomization, compared with 10% in Latin America. North America had the highest rates of temporary study drug discontinuation and procedures. Time in therapeutic range (INR 2.0–3.0) on warfarin was highest in North America and lowest in Asia Pacific. After adjustment and compared with Europe, patients in Asia Pacific had 2-fold higher risk of stroke/systemic embolism and 3-fold higher risk of intracranial hemorrhage. Patients in Latin America had 2-fold increased risk of all-cause death compared with Europe. The benefits of apixaban compared with warfarin were consistent across regions; there was a pronounced reduction in major bleeding in patients from Asia Pacific compared with other regions (p-interaction = 0.03). Conclusions: Patients with AF enrolled in prespecified regions in ARISTOTLE had differences in clinical baseline characteristics and practice patterns. After adjustment, patients in Asia Pacific and Latin America had worse outcomes than patients from other regions. The relative benefits of apixaban compared with warfarin were consistent across regions with an even greater treatment effect in the reduction of bleeding in patients from Asia Pacific. Highlights: In patients with AF, there are differences in patient characteristics and practice patterns by region. Patients in the Asia Pacific region had worse outcomes than patients in other regions. There is an even greater benefit of less bleeding with apixaban than warfarin in patients from Asia Pacific.